Application of multiple linear regression in certain chemical characteristics of soy-based spread - Nurhazwani Jantraz; Robiah Adnan; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2010